2020
DOI: 10.1007/s00158-020-02736-8
|View full text |Cite
|
Sign up to set email alerts
|

Topology design of two-fluid heat exchange

Abstract: Heat exchangers are devices that typically transfer heat between two fluids. The performance of a heat exchanger such as heat transfer rate and pressure loss strongly depends on the flow regime in the heat transfer system. In this paper, we present a density-based topology optimization method for a two-fluid heat exchange system, which achieves a maximum heat transfer rate under fixed pressure loss. We propose a representation model accounting for three states, i.e., two fluids and a solid wall between the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…[101]- [105]. For instance, Kobayashi et al The density-based method has shown its high efficiency by avoiding the re-meshing process at each iteration.…”
Section: Density-based Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[101]- [105]. For instance, Kobayashi et al The density-based method has shown its high efficiency by avoiding the re-meshing process at each iteration.…”
Section: Density-based Methodsmentioning
confidence: 99%
“…[59]- [62], [64]- [78], [80], [82]- [84], [86], [89], [91], [94]- [100], [103]- [105], [116]- [119], [121], [122], [136]- [138]. As for the single-flow HXs, for instance, Dede et al…”
Section: Finite Element Methods (Fem)mentioning
confidence: 99%
See 1 more Smart Citation
“…The topology optimization of such systems proves quite challenging, in part due to the modelling and the implementation of a non-mixing constraint between different input channels. It has been an active research issue since the seminal MSc thesis [76], see notably the recent works [80,48,81,79,87,58] and the introduction in [54] for an overview.…”
Section: Introductionmentioning
confidence: 99%
“…Several approaches have been proposed in the aforementioned works to circumvent this drawback, e.g. : the use of a fluid-tracking model in [76,87], that of a suitable interpolation scheme in [58], or of a filter enforcing a solid coating around each fluid phase [48,54]. One of the common difficulties of this class of methods is the selection of appropriate metaparameters which penalize sufficiently the porous interfaces between the two fluids but which also ensure that the inlets are indeed connected to the outlets [54].…”
Section: Introductionmentioning
confidence: 99%